Dealloying Synthesis of Silicon Nanotubes for High‐Performance Lithium Ion Batteries. Issue 9 (30th March 2022) - Zhao, Jinfu; Wei, Wenxian; Xu, Na; Wang, Xiaotong; Chang, Limin; Wang, Li; Fang, Luan; Le, Zaiyuan; Nie, Ping
Abstract: Practical applications of silicon‐based anodes in lithium ion batteries have attracted unprecedented attentions due to the merits of extraordinary energy density, high safety and low cost. Nevertheless, the inevitable huge volume change upon lithiation and delithiation brings about silicon electrode integrity damage and fast capacity fading, hampering the large‐scale application. Herein, a novel one‐dimensional tubular silicon‐nitrogen doped carbon composite (Si@NC) with a core‐shell structure has been fabricated using silicon magnesium alloy and polydopamine as a template and precursor. The as‐obtained composite exhibits remarkable specific capacity and ultrafast redox kinetics, an outstanding cycling stability with fine capacity of 583.6 mAh g −1 at 0.5 A g −1 over 200 cycles is delivered. Moreover, a full cell matched with LiFePO4 cathode has demonstrated a reversible capacity of 148.8 mAh g −1 with high Coulombic efficiency as well as an excellent energy density of 396 Wh kg −1 . The nanotube structure engineering and silicon confined in nitrogen doped carbon effectively alleviate the volume expansion and endow the composite with superior stability. The robust strategy developed here gives a new insight into designing silicon anodes for enhanced lithium storage properties. Abstract : Silicon nanotubes confined in nitrogen doped carbon nanocomposites designed by a simple dealloying strategy are reported. The nanotube engineering endows silicon anodes with low particle expansion upon lithiation, rapid ion/electron diffusion, remarkable specific discharge capacity and outstanding cycling performance.